2019
DOI: 10.3390/ijms20143520
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Brown Adipocyte Autophagy Improves Energy Metabolism by Regulating Mitochondrial Turnover

Abstract: The high abundance of mitochondria and the expression of mitochondrial uncoupling protein 1 (UCP1) confer upon brown adipose tissue (BAT) the unique capacity to convert chemical energy into heat at the expense of ATP synthesis. It was long believed that BAT is present only in infants, and so, it was not considered as a potential therapeutic target for metabolic syndrome; however, the discovery of metabolically active BAT in adult humans has re-stimulated interest in the contributions of BAT metabolic regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 71 publications
(86 reference statements)
1
23
0
Order By: Relevance
“…It has been reported that deletion of the gene essential for autophagosome assembly, Atg7, in brown adipose tissue results in elevated levels of UCP1 [ 95 , 96 ] and improved metabolic health, as does deletion of the mitophagy-initiating protein Parkin [ 91 ]. Similarly, the whitening of brite/beige adipocytes is an autophagy-dependent process [ 46 , 47 , 70 ], and deletion or inhibition of key components of the autophagy pathway such as Atg5, Atg12, or Park2 results in elevated mitochondrial content and UCP1 levels [ 46 , 47 , 70 , 92 , [96] , [97] , [98] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that deletion of the gene essential for autophagosome assembly, Atg7, in brown adipose tissue results in elevated levels of UCP1 [ 95 , 96 ] and improved metabolic health, as does deletion of the mitophagy-initiating protein Parkin [ 91 ]. Similarly, the whitening of brite/beige adipocytes is an autophagy-dependent process [ 46 , 47 , 70 ], and deletion or inhibition of key components of the autophagy pathway such as Atg5, Atg12, or Park2 results in elevated mitochondrial content and UCP1 levels [ 46 , 47 , 70 , 92 , [96] , [97] , [98] ].…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have reported increased mitochondrial mass upon genetic or pharmacological inhibition of autophagy and mitophagy in brite/beige or brown adipocytes [ 46 , 47 , 91 , 95 , 102 ]. While these models result in beneficial metabolic effects such as increased oxygen consumption, protection from diet-induced obesity, and insulin resistance, we did not observe advantageous effects on systemic metabolism caused by higher UCP1 levels and mitochondrial mass in BAT of the TFEB BAT KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the control mice, PHA-treated mice showed a sizeable increase in oxygen consumption during the dark cycle (active phase), and there was no significant difference between PHA and control groups during the light cycle (non-active phase). BAT activity is positively correlated with energy expenditure and can improve glucose metabolism ( Kim et al . 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Upon adipose-specific deletion of Atg7, WAT acquires functional (but not transcriptional) features of BAT, including an increase in the mitochondrial content and oxidative metabolism [ 82 ]. Similarly, the suppression of autophagy in BAT improves energy usage, while limiting the obese phenotype [ 83 ]. Mechanistically, these effects can be attributed to the inhibition of mitophagy, which in turn restrains the WAT to BAT conversion while reinforcing BAT metabolic peculiarities.…”
Section: Autophagy Between Obesity and Oxidative Stressmentioning
confidence: 99%